Numerical analysis of marangoni natural convection of corium in a semi-cylindrical cavity in the presence of a boundary condition of the third kind on the bottom wall - Khatab Shoruk Abdelzaher Mesilkhi Mohamed S. A. (2024, 2024)
Заглавие с экрана